Peripheral defocus of myopic eyes corrected with Perifocal-M glasses, monofocal glasses, and soft contact lenses - E. P. Tarutta; N. A. Tarasova; O. V. Proskurina; S. V. Milash; N. Yu. Kushnarevich; N. V. Khodzhabekyan (Российский офтальмологический журнал)
The purpose of the work was to study peripheral refraction in myopic patients without correction, in soft contact lenses (SCL), in monofocal glasses, and in Perifocal-M glasses.Material and methods. A total of 97 patients (184 eyes) aged 9–18 years with various degrees of myopia were examined. The peripheral refraction was measured using a Grand Seiko WR-5100K binocular open-field autorefractometer without correction, in glasses, and in the SCL. For the eviation of gaze, a nozzle was designed, which was attached to the device stand at a distance of 50 cm from the patient's eyes. On the nozzle, there were 4 marks for fixing the gaze in the position of 15° and 30° to the nose (N) and to the temple (T) from the central position.Results. In patients with myopia of various degrees without correction and with correction by monofocal glasses, hyperopic defocus formed in all zones on average. In eyes that were corrected with SCL and were mildly myopic in all zones, hyperopic defocus was detected. In moderate myopia, myopic defocus was detected in the zones T30° and N30°. With a high degree of myopia, myopic defocus was detected on the periphery in all zones except T15°, reaching -2.23 ± 1.35 D in the T30° zone and -1.56 ± 0.82 D in the N30° zone. In Perifocal-M glasses, myopic defocus formed in mildly myopic eyes: in the T15° zone its value was -0.95 ± 0.12 D, -0.24 ± 0.05 D in the N15° zone, and -1.14 ± 0.13 D in the T30° zone. Hyperopic defocus was observed only in the zone at N30°, and its value was minimal compared to other types of correction which was 0.13 ± 0.05 D. In moderate myopia, myopic defocus was observed only in the zone N15° at -0.28 ± 0.04 D. In all other zones, hyperopic defocus remained, but its magnitude was minimal compared to monofocal glasses: 0.6 ± 0.1 D at T30°, 0.05 ± 0.04 D at T15°, and 0.74 ± 0.11 D at N30°. Conclusion. In relation to peripheral defocus, perifocal glasses have an advantage in correcting myopia of a low and, in part, moderate degree.